HEALTH CRISIS MANAGEMENT: A STUDY ON THE HANDLING OF SCABIES AS A COMMUNICABLE DISEASE AT AL HUSAIN ISLAMIC BOARDING SCHOOL - Hidayati, Aini; Nurul Isnaini Febriarini (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Islamic boarding schools are densely populated, communal environments that are highly susceptible to the spread of communicable diseases such as scabies. This study aims to analyze the effectiveness of health crisis management in addressing scabies outbreaks at Al Husain Islamic Boarding School in Magelang.This research employed a quantitative approach using path analysis based on Structural Equation Modeling (SEM) with SmartPLS 3.0. A total of 220 students were selected as respondents using the Slovin formula. Data were collected through a structured questionnaire.The findings indicate that the variables of policy and protocol had the most significant influence on response speed and the overall effectiveness of crisis management (β = 0.279; p = 0.000). Response speed also served as a key mediating factor, strengthening the relationship between healthcare access and the effectiveness of crisis management (β = 0.145; p = 0.004). Conversely, the variables of health education and housing density did not show a significant impact. The effectiveness of health crisis management in Islamic boarding schools is influenced by a combination of robust policies, rapid response, and adequate healthcare access. Structural interventions and strengthened response systems are essential for the prevention of scabies outbreaks.